Durable and highly sensitive flexible sensors for wearable electronic devices with PDMS-MXene/TPU composite films. Issue 4 (15th February 2022) - Zhang, Zhennan; Weng, Ling; Guo, Ke; Guan, Lizhu; Wang, Xiaoming; Wu, Zijian
Abstract: MXenes, as two-dimensional (2D) transition metal carbides, carbonitrides, and nitrides, have very excellent electrical properties and surface activity and are increasingly used in supercapacitors, batteries, electromagnetic interference shielding, and composite materials. Still, the poor stability of MXene when exposed to aqueous oxygen and the poor ability to interact with the polymer matrix have become important factors limiting its' practical applications. To enhance stability, highly conductive and stretchable Ti3 C2 MXene/TPU sensing elements were prepared by a simple spraying process using thermoplastic polyurethane (TPU) as a substrate, and the sensing elements were encapsulated by polydimethylsiloxane (PDMS) to obtain MXene-TPU/PDMS constructed flexible strain sensors with excellent performance. This strain sensor features low detection limits (less than 0.005%, 0.5 μm), a wide sensing range (0–90%), a short response time (120.1 ms), and excellent durability (>3000 cycles). This strain sensor can be applied to a range of applications such as health detection, motion signals, detection of robot movements, and wearable electronic devices.